Status Hukum Papua Barat: The Right to Self-Determination atau National Integrity? - Fiona, Sehrenneta Bella; Kusniati, Retno (Faculty of Law, Universitas Jambi, 2020)
West Papua as one of the regions in Indonesia that integrates with the New York Agreement between Indonesia and the Netherlands carries the right of self-determination in an effort to separate from Indonesia. This research discusses how the regulation of the right to self-determination as part of Human Rights and examines the basis of West Papua in carrying out the right to self-determination and declaring itself as a state. This type of research is normative, with statutory (statue) and historical approaches. This research concludes that the right to self-determination is part of human rights, while West Papua’s claim as part of the Indonesian State in demanding the right to self-determination is clashed with the Uti Possidetis Juris and Territorial Integrity.